Systematic Description of Ammonites from the Jumara Formation at Jara Dome, Kachchh Mainland - Rinku A. Patel,; Paras M. Solanki, (International Journal of Scientific Research in Science and Technology, 2025)
The Jara Dome, situated in the Lakhpat Taluka of Kachchh District, Gujarat, represents a significant geological structure within the Kachchh Mainland and provides exceptional exposure of Middle to Upper Jurassic strata. This study documents ammonite-bearing horizons within the Dhosa Oolite Member of the Jumara Formation, composed of fossiliferous oolitic limestones interbedded with shales and ferruginous beds. Detailed field investigations and systematic sampling yielded five ammonite taxa, all recovered from stratigraphically constrained intervals. Taxonomic identification was conducted through comparative morphological analysis, revealing a diverse assemblage that contributes to refining the biostratigraphic framework of the region. The presence of genera such as Perisphinctes, Cadoceras, and Macrocephalites provides key insights into ammonoid evolution and regional stratigraphic correlation. Structurally, the study area is influenced by the Kachchh Mainland Fault and associated neotectonic activity, which have played a role in shaping the sedimentary and structural architecture of the Jara Dome. The integration of paleontological, stratigraphic, and structural data enhances our understanding of Jurassic depositional environments and basin evolution in western India.
Keywords: Ammonites; Jumara Formation; Jara Dome; Western Kachchh; Gujarat; India